# How do you solve #\frac { 1} { 3} x + \frac { 5} { 6} = \frac { 1} { 6} x - \frac { 1} { 2}#?

#{: ("Left Side",color(white)("XX"),"Right Side"), (1/3x+5/6,,1/6x-1/2), (,"with "x=-8,), (=((-8)/3+5/6),,=(-8)/6-1/2), (=(-16+5)/6,,=(-8-3)/6), (=-11/6,,=-11/6) :}#

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation (\frac{1}{3}x + \frac{5}{6} = \frac{1}{6}x - \frac{1}{2}), first, combine like terms. Subtract (\frac{1}{3}x) from both sides to isolate the variable term on one side. Then, add (\frac{1}{2}) to both sides to move constant terms to the other side. After that, solve for (x). The solution is (x = -3).

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- X varies inversely as the square of y, and x=3 when y=20, what is the equation?
- How do you simplify #(c+4)/(c-4)#?
- If y varies directly as z and inversely as x and y = 27 and z = -3 when z = 2, how do you find x when y = 9 and z = -5?
- How do you simplify #(2x - 4)/ (x^2 - 3x + 2) times (x^2 - 4x)/4#?
- How do you solve #3/x+x=4#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7